2018
DOI: 10.1016/j.optcom.2018.07.065
|View full text |Cite
|
Sign up to set email alerts
|

A wide-angle shift-free metamaterial filter design for anti-laser striking application

Abstract: Peer reviewed versionCyswllt i'r cyhoeddiad / Link to publication Dyfyniad o'r fersiwn a gyhoeddwyd / Citation for published version (APA): Monks, J., Yue, L., Yan, B., Aldred, B., Hurst, A., & Wang, Z. (2018). A wide-angle shift-free metamaterial filter design for anti-laser striking application. Optics Communications, 429, 53-59.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Such a beating-free oscillatory nature in the spectrum indicates a high repeatability of the growth process for all the GZO oxide layers of the S0 multilayer in both thickness and structure. It can be noticed that adjusting the optical properties of multilayer structures by a certain optimization of the thicknesses of oxide and metal interlayers makes it possible to use such structures for antilaser striking (optical filters) and laser-induced THz radiation source applications [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…Such a beating-free oscillatory nature in the spectrum indicates a high repeatability of the growth process for all the GZO oxide layers of the S0 multilayer in both thickness and structure. It can be noticed that adjusting the optical properties of multilayer structures by a certain optimization of the thicknesses of oxide and metal interlayers makes it possible to use such structures for antilaser striking (optical filters) and laser-induced THz radiation source applications [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, thin film dielectric stacks have formulated the solution for filtering light in a multitude of fashions [20] . However, in recent years it has been shown that optical metamaterials could also provide a solution for filtering light [21] . Dielectric thin film filters are an excellent technology that will not be surpassed with ease.…”
Section: Applicationsmentioning
confidence: 99%
“…The strong electric and magnetic responses lead to an impedance mismatch and angular stability and can be driven by absorption [21] . Therefore, the requirement to engineer nanoparticles absorption responses become necessary to solve such solutions and to formulate the metamaterials building blocks.…”
Section: Applicationsmentioning
confidence: 99%
“…This in turn creates further problems through reduced visibility (decrease in transmission) and high coloration. Therefore, it has become highly desirable to find a solution that is capable of combating the limits found in standard thin-film technology [4].…”
Section: Introductionmentioning
confidence: 99%